Krausism and other historical referential models in Costa Rican music education: Los cantos escolares (1888) by Juan Fernández Ferraz and José Campabadal - Ramón-Salinas, Jorge; Zavala Arnal, Carmen M. (Historia y Memoria de la Educación, 2025)
The present article aims to study the Cantos Escolares (School Songs) (1888) by Juan Fernández Ferraz (1849-1904) and José Campadabal (1849-1905), a widely disseminated school songbook in Costa Rica, created by two Spaniards who settled in the country and became key figures in education and culture in the young republic. The objective is to reflect, beyond the specific musical aspect, on the scope and meaning of this selection of songs, which synthesized essential educational and moral aspects upon which the republic was considered to be built. Initially, a broad contextualization of the work and its authors is provided, taking into account ideological and musical factors. An analysis of existing studies is conducted, going beyond specifically musical aspects in order to highlight the importance and significance of collective singing development in the social sphere and in Costa Rican education during the second half of the nineteenth century. Different educational initiatives are described in which songs, transformed into relevant didactic tools, serve as an ideal vehicle to create supporters, advocates of a nascent nation. It can be concluded that the relevance of this songbook surpasses its mere educational and musical document status, as it represents a work of documentary value. Despite its obvious limitations as outdated and colonial material for teaching music, it acquires valuable significance from a historiographic and sociological perspective within the historical trajectory of Costa Rican education.